Rapid Quantitation of Gene Therapy Specific CFTR Expression Using the Amplification Refractory Mutation System. (July 1999) - Thorpe, Peter H.; Porteous, David J.
Gene therapy offers the potential of correcting genetic disorders such as cystic fibrosis (CF). By complementing the nonfunctional endogenous cystic fibrosis transmembrane conductance regulator ( CFTR ) gene with a functional transgene, we anticipate it may alleviate the disease phenotype. All approaches to CF gene therapy rely upon sensitive assays to monitor delivery, expression and maintenance of CFTR vectors. Here, we describe the adaptation of the amplification refractory mutation system (ARMS) to discriminate between different forms of CFTR . A LightCycler TM PCR machine allows realtime continuous fluorescence monitoring of rapid-cycle PCR. We show quantitation of and discrimination between expression of endogenous (wild-type or mutant) CFTR and the introduced transgene.